Полет над разлукой: роман / А. Берсенева - Берсенева Анна (Под знаком любви, 2007)
Экземпляры: ф.2 (2008) / Инвентарный номер: 52302 / Цена: / Сис.шифр: 84(2Рос=Рус)6^VLBC/RL / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6^VLBC/RL